THE IMPLEMENTATION OF EXTRA JURISDICTION HIJACKING - Muhammad Rafi Darajati (Law Faculty of Universitas Bandar Lampung, 2023)
Plane hijacking is a relatively new form of crime; the motives behind the hijacking varied, ranging from economic to political. The international community considers that acts of hijack can threaten international peace and security. This article aims to discuss the efforts of the international community in the fight against this aircraft hijacking crime. The results showed that the international community's efforts were to make various conventions to protect international aviation activities. In the convention, the international community made various efforts to prevent and eradicate aircraft hijacks, such as allowing each country to expand its jurisdiction.